Graphene and Selected Derivatives as Negative Electrodes in Sodium‐ and Lithium‐Ion Batteries. Issue 4 (4th February 2015) - Pramudita, James C.; Pontiroli, Daniele; Magnani, Giacomo; Gaboardi, Mattia; Riccò, Mauro; Milanese, Chiara; Brand, Helen E. A.; Sharma, Neeraj
Abstract The performance of graphene, and a few selected derivatives, was investigated as a negative electrode material in sodium‐ and lithium‐ion batteries. Hydrogenated graphene shows significant improvement in battery performance compared with as‐prepared graphene, with reversible capacities of 488 mA h g−1 for lithium‐ion batteries after 50 cycles and 491 mA h g−1 for sodium‐ion batteries after 20 cycles. Notably, high rates of 1 A g−1 for graphene and 5 A g−1 for hydrogenated graphene indicate higher capacities in sodium‐ion batteries than in lithium‐ion batteries. Alternatively, nickel‐nanoparticle‐decorated graphene performed relatively poorly in lithium‐ion batteries. However, in sodium‐ion batteries they showed the highest reversible capacities of all studied batteries and graphene derivatives, with 826 mA h g−1 after 25 cycles with ≈97 % coulombic efficiency. Overall, minor modifications to graphene can dramatically improve electrochemical performance in both lithium‐ion and sodium‐ion batteries.